ANALISIS DAN PERANCANGAN SPK PEMILIHAN PNS TELADAN DENGAN METODE SAW PADA BKD PROVINSI JAMBI - Sigit Eka Karsa; Joni Devitra (LPPM Universitas Dinamika Bangsa, 2017)
Regional Personnel Agency (BKD) the Jambi provincial government is an organization that handlesaffairs - affairs staffing environment Jambi provincial government, one election silyl exemplary publicservant. For example the selection of civil servants still use the registry system manually. Theninvestigated and corrected if these employees deserve to be exemplary civil servants. After that didapatlahlist of names - names of employees eligible. Then sealed by officials echelon existing at BKD Jambiprovincial government. So the authors designed a system that can assist and facilitate the leadership inmaking decisions in the selection of civil servants exemplary. To help the decision-making system usingfuzzy logic decisions. The results of this system design can facilitate BKD Head of Jambi province, andalso can shorten the time civil servants exemplary election.